2008
DOI: 10.1063/1.3013449
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and diffusion during growth of ternary Co1−xNixSi2 thin films studied by complementary techniques in real time

Abstract: Simultaneous real-time x-ray diffraction spectroscopy, Rutherford backscattering spectrometry, and sheet resistance measurements to study thin film growth kinetics by Kissinger plots J. Appl. Phys. Nanostructure and giant Hall effect in TM x ( Si O 2 ) 1 − x ( TM = Co , Fe , Ni ) granular system J. Appl. Phys. 99, 08C511 (2006); 10.1063/1.2171013 High-temperature degradation of NiSi films: Agglomeration versus Ni Si 2 nucleation J. Appl. Phys. 98, 033526 (2005); 10.1063/1.2005380 High-resolution investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…NiSi 2 , is the enhanced formation of the disilicide Co 1-x Ni x Si 2 from a CoSi/NiSi mixture and the delayed nucleation of NiSi 2 from a Ni 1-x Pt x Si solid solution. [5][6][7] The presence of the isomorphous phases NiSi 2 and CoSi 2 on the one hand and NiSi and PtSi on the other hand is crucial to allow solid solubility and, consequently, to affect the sign of DS. As NiSi and PtSi, PdSi also shares the same crystal structure and alloying Ni with Pd has been shown to delay NiSi 2 nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…NiSi 2 , is the enhanced formation of the disilicide Co 1-x Ni x Si 2 from a CoSi/NiSi mixture and the delayed nucleation of NiSi 2 from a Ni 1-x Pt x Si solid solution. [5][6][7] The presence of the isomorphous phases NiSi 2 and CoSi 2 on the one hand and NiSi and PtSi on the other hand is crucial to allow solid solubility and, consequently, to affect the sign of DS. As NiSi and PtSi, PdSi also shares the same crystal structure and alloying Ni with Pd has been shown to delay NiSi 2 nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…The leading side of silicidation shows a composition of Ni 50 Co 10 Si 40 , a metal rich composition Me 3 Si 2 , similar to the results in Figure 3. In addition, the trailing side has a composition of Ni 40 Si 40 Si 20 , also same as in Figure 3, i.e. Me 4 Si.…”
Section: Resultsmentioning
confidence: 87%
“…21,24,[37][38][39][40][41][42][43][44] Although the interest was later shifted to the nickel monosilicide for that application, the ternary silicide was then of interest as alternative to CoSi 2 because the addition of Ni improves the nucleation of Co disilicide and reduces the silicide roughness and Si consumption. Therefore, not only all those studies 21,24,[37][38][39][40][41][42][43][44] were based on vacuum deposited extremely thin films but also most of them focused on the disilicide formation from Co rich alloys at high temperatures above 500…”
Section: Resultsmentioning
confidence: 99%
“…6 and 51.2 , respectively, and CoSi 2 (220) at 47. 9 . The ramped thermal anneals from room temperature to 900…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…6 While the formation temperature for binary CoSi 2 is reasonably well defined, it has been shown that the onset temperature can be raised or lowered by alloying Co with elements such as Ni, Fe, Ti, and W (Refs. [7][8][9] or by the insertion of an Au or Ti layer. [10][11][12] Another interesting feature of CoSi 2 is its cubic CaF 2 structure with a lattice constant which differs from that of Si by only À1.2% making is possible, in principle, for CoSi 2 to grow epitaxially on silicon single crystal substrates.…”
Section: Introductionmentioning
confidence: 99%